American theatre : a chronicle of comedy and drama, 1969-2000 - Hischak, Thomas S. (Oxford University Press, 2001)
Volume Four of the distinguished American Theatre: A Chronicle of Comedy and Drama series offers a thorough, candid, and fascinating look at the theater in New York during the last decades of the twentieth century.